2005
DOI: 10.1038/sj.onc.1208446
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Gingerol inhibits COX-2 expression by blocking the activation of p38 MAP kinase and NF-κB in phorbol ester-stimulated mouse skin

Abstract: [6]-Gingerol, a pungent ingredient of ginger (Zingiber officinale Roscoe, Zingiberaceae), has a wide array of pharmacologic effects. The present study was aimed at unraveling the molecular mechanisms underlying previously reported antitumor promoting effects of [6]-gingerol in mouse skin in vivo. One of the well-recognized molecular targets for chemoprevention is cyclooxygenase-2 (COX-2) that is abnormally upregulated in many premalignant and malignant tissues and cells. In our present study, topical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(201 citation statements)
references
References 55 publications
8
188
1
4
Order By: Relevance
“…The hyperplasia in DMBA-treated skin was associated with increasingly higher levels of COX-2 expression, an enzyme associated with inflammation and tumorigenesis (26). As shown in Fig.…”
Section: Analysis Of Mutations In Codon 61 Of Ha-ras Oncogene In Skinmentioning
confidence: 73%
“…The hyperplasia in DMBA-treated skin was associated with increasingly higher levels of COX-2 expression, an enzyme associated with inflammation and tumorigenesis (26). As shown in Fig.…”
Section: Analysis Of Mutations In Codon 61 Of Ha-ras Oncogene In Skinmentioning
confidence: 73%
“…2 indicated that Ucn1-regulated ICAM1 expression was dependent on COX2. Moreover, Kim et al (2005) found that the induction of COX2 in mouse skin is regulated, at least in part, by an eukaryotic transcription factor NF-kB. Therefore, we examined the effects of PDTC on COX2 expression.…”
Section: Pka-creb Participated In the Signaling Events Leading To Indmentioning
confidence: 99%
“…Tais estudos incluem o papel dos compostos na atividade motora, efeito antipirético, analgésico (SUEKAWA et al, 1984), antioxidante (MASUDA et al, 2004), inibidor da angiogênese (KIM et al, 2005), inibidor de metástase de câncer de mama (LEE et al, 2008), antibacteriano (PARK;LEE, 2008), além das atividades imunomoduladoras e anti-inflamatórias que serão tratadas no presente trabalho. Há também estudos abordando suas propriedades físicas (DING et al, 1991) Dentre os componentes, destacam-se o 6-gingerol e o 6-shogaol e gingerdiones, que representam 3% do óleo volátil, sendo os mais abundantes componentes da raiz (ZICK et al, 2008;VRIENS et al, 2008), motivo pelo qual são atualmente as moléculas mais exploradas individualmente (SAHA et al, 2014;KUMAR et al, 2014;DUGASANI, 2010;GAUS et al, 2009;TRIPATHI et al, 2007;ALI el al., 2007;KOH et al, 2009).…”
Section: Gengibre E Seus Componentesunclassified
“…Porém os autores demonstraram que estes mecanismo parece estar relacionado com a interação com a via das MAP quinases com NFkB, em que a MAP quinase p38 ao ser inibida pelo 6-gingerol levava a não fosforilação do IkB-α e da subunidade p65. Culminando assim com a diminuição dos níveis de COX-2 (KIM et al, 2005). Kim et al (2005) demonstraram que o 6-gingerol reduziu os níveis de COX-2, inibiu a translocação da subunidade p65 para o núcleo, e também a inibição da fosforilação do complexo IkB-α em modelos de exposição de cultura de queratinócitos humanos e camundongos hairless à radiação UVB (KIM et al, 2007).…”
Section: Efeito Anti-inflamatório Do Gengibre: Possível Via De Sinaliunclassified